Analysis and compensation of ADCP current direction error caused by ambient magnetic field. (December 2016) - Dai, Hao; Shang, Shaoping; He, Zhigang; Liu, Ke
Abstract: Internal magnetic compasses of acoustic Doppler current profilers (ADCPs) are easily disturbed by significant amount of hard/soft iron in some moorings or ships, causing the significant current direction error. In this paper, with the consideration of the roll and pitch of ADCPs mounted on moorings or ships, we deduce and derive the quantitative relationship between the magnetic deviation and its induced current direction error. According to the relationship and the characteristic model of the magnetic deviation, the compensated coefficients are calibrated on the spot and applied to compensate the subsequent current observation. Compared with the current direction without the magnetic deviation affection, the measured current direction accuracy evaluated by the root mean square error improves remarkably. From the experimental result, the approach is proved to be effective for correcting the fixed-point current direction measurement of ADCPs, which are affected by the magnetic deviation and in the small tilt condition. Highlights: The quantitative relationship between the magnetic deviation and its induced current direction error is deduced and derived. The approach for calibrating the coefficients on the spot and compensating the current direction error is proposed. The approach's effect for compensating is remarkable, with the root mean square error as the evaluation standard.